Condition of coral reef in Batee Island waters, Peukan Bada Sub-District, Aceh Besar - Maria Ulfah; Saiful Mahlil; Muhammad Nasir; Sayyid Afdhal El Rahimi; Syahrul Purnawan; Muhammad Rizki Fazillah (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
Batee Island is one of the small islands in the Aceh Besar region and is uninhabited and directly faces the Indian Ocean. Batee Island's waters have the potential for marine biota, especially coral reef ecosystems, and other associated biotas. This study aims to determine the percentage and comparison of live coral cover in Batee Island waters and determine the genus' composition in Batee Island waters. This research was conducted in October-November 2016. Collecting coral reef data using the LIT (Line Intercept Transect) method. The results showed that the live coral cover in Batee Island's waters differed between the East and West Batee Islands. The coral reefs' average condition in Batee Island waters at shallow depths (0-5m) is 41.41%, and deep (6-10m) is 36.52%. Overall, the conditions and live coral cover in the waters of Batee Island are classified as moderate. In the waters of Batee Island, there are 31 coral genera. The highest percentage of corals was the genus Acropora (50.02%).Keywords:Batee IslandConditionCoral reefCoral cover